Malawi Economic Monitor, November 2018 : Investing in Girls' Education - World Bank (World Bank, Lilongwe, Malawi, 2018)
The Malawi Economic Monitor (MEM) provides an analysis of economic and structural developmentissues in Malawi. This edition was published in November 2018. It follows seven previous editions of the MEM and is part of an ongoing series, with future editions to follow twice each year.The aim of the publication is to foster better-informed policy analysis and debate regarding the key challenges that Malawi faces in its endeavor to achieve high rates of stable, inclusive andsustainable economic growth. The MEM consists of two parts: Part 1 presents a review of recent economic developments and a macroeconomic outlook. Part 2 focuses on a special topic relevant to Malawi’s development prospects. In this edition, the special topic focuses on ending child marriages and early childbearing as well as improving girls’ level of educational attainment.Despite substantial progress over the last two decades, girls still have lower average levels ofeducational attainment than boys at the secondary level in many countries. This is also the case inMalawi, partly because many girls marry or have children before the age of 18, often before they are physically and emotionally ready to become wives and mothers. Educating girls, ending child marriage, and preventing early childbearing are all essential to ensure that girls have agency, not only as future wives and mothers, but also as productive citizens in a wide range of roles. These are also enablers for countries to achieve their full development potential, which requires the full participation of all citizens to the degree to which they are capable. The failure to empower women to participate therefore represents a lost opportunity. This MEM documents trends in child marriage, early childbearing and girls’ low average levels of educational attainment, with an examination of their impacts on a wide range of development outcomes. It includes estimations of the economic costs of child marriage and proposes a range of policy options to improve opportunities for adolescent girls.